The Significance and Importance of dPCR, qPCR, and SYBR Green PCR Kit in the Detection of Numerous Diseases - Shahrajabian, Mohamad Hesam; Sun, Wenli (Current Pharmaceutical Design, 2024)
Digital PCR (dPCR) is the latest technique that has become commercially accessible for various types of research. This method uses Taq polymerase in a standard polymerase chain reaction (PCR) to amplify a target DNA fragment from a complex sample, like quantitative PCR (qPCR) and droplet digital PCR (dd- PCR). ddPCR may facilitate microRNA (miRNA) measurement, particularly in liquid biopsy, because it has been proven to be more effective and sensitive, and in this method, ddPCR can provide an unprecedented chance for deoxyribonucleic acid (DNA) methylation research because of its capability to increase sensitivity and precision over conventional PCR-based methods. qPCR has also been found to be a valuable standard technique to measure both copy DNA (cDNA) and genomic DNA (gDNA) levels, although the finding data can be significantly variable and non-reproducible without relevant validation and verification of both primers and samples. The SYBR green quantitative real-time PCR (qPCR) method has been reported as an appropriate technique for quantitative detection and species discrimination, and has been applied profitably in different experiments to determine, quantify, and discriminate species. Although both TaqMan qRT-PCR and SYBR green qRT-PCR are sensitive and rapid, the SYBR green qRT-PCR assay is easy and the TaqMan qRT-PCR assay is specific but expensive due to the probe required. This review aimed to introduce dPCR, qPCR, SYBR green PCR kit, and digital PCR, compare them, and also introduce their advantages in the detection of different diseases.
Keywords: nucleic acid detection